Physical education lessons improve physical fitness and functional mobility in rural children with limited participation in regular physical activities: comparison of integrated neuromuscular training and core stabilization training - Kabasakal Sema Arslan (Biomedical Human Kinetics)
Study aim: It is crucial for children to thrive and grow up healthy, but without adequate physical fitness and mobility, this can be difficult to attain. Unfortunately, those living in rural areas are at a particular disadvantage when it comes to access to regular physical activity. However, by including exercise programs in the physical education lessons curriculum, these children can be provided with the opportunity to develop these crucial attributes. This study aims to investigate and compare the effects of core stabilization training (CST) and integrated neuromuscular training (INT) applied in physical education lessons on children’s physical condition and functional mobility.